Program Bantuan Pendampingan Pengurusan Sertifikasi Halal Gratis Bagi Umkm Bersama Mahasiswa IAI Tazkia - Indra, Indra; Rahman, Arip; Akbar, Nashr (Tazkia Islamic University College, 2025)
In 2024, halal certification for business actors will become mandatory based on Law No. 33 of 2014 concerning Halal Product Guarantees, which is also enhanced by Law No. 11 of 2020 concerning Job Creation. However, in practice, there are several obstacles faced by MSMEs in carrying out these obligations, such as; costs, access to information and knowledge for MSMEs, and the process of digitizing halal certification which MSME players do not easily understand. Therefore, this program aims to assist MSMEs in processing halal certification. The target in this first stage is five MSMEs in Bogor City/Regency, which will involve IAI Tazkia students as the accompanying team. The service method used in this community service program is service learning.